The Effect Of Liquidity, Profitability, Capital Structure Of Corporate Values In Mining Sector In Indonesia - Lukmanul Hakim Aziz (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This research aimed to analyze the effect of liquidity, profitability, capital structure to the company's value in the mining sector companies listed on the Indonesia Stock Exchange in 2010 until 2014. The population of this research is mining coal mining sub-sector, sub-sector of crude petroleum and natural gas production, sub-sector of metal and mineral mining, and sub-sectors land / stone quarrying. Samples were taken by using purposive sampling method so acquired 7 companies which qualify as samples. This study uses analysis tools Partial Least Square (PLS). PLS is one of the statistical methods SEM-based variant that serves to determine the effect of exogenous variables consisting of proxies current ratio, quick ratio, ROA, ROE on capital structure and corporate value. The results of this study indicate that there is an influence on the variables of liquidity, profitability of the capital structure. And there is an influence on the profitability of the company's value. While the liquidity variables to the value of the company does not have a significant effect. Liquidity and profitability through capital structure to the value of the company does not have a significant effect.